Plaque rupture - Kovanen, Petri (Henry Stewart Talks, 2008)
Inflammation and aetherosclerosis, Immune activation, Response to injury hypothesis, Discovery of the pathophysiology of aetherosclerosis, The cholesterol era, The LDL level, Arterial intima: the site of atherogenesis, Genesis of thickening intima, Adaptive intimal thickening, Topology of coronary athero-sclerotic lesions, Cholesterol in blood and in coronary arterial wall, The "bad" LDL cholesterol and the "good" HDL cholesterol: an imbalance, Coronary artery disease, LDL-driven atherosclerosis leads to coronary stenosis |Human coronary atheroma, Atherothrombosis, Plaque disruption, Structure of an LDL particle, Extracellular aggregated and fused LDL particles in the arterial intima of genetically hyperlipidemic mouse, Extracellular lipid droplets in human atherosclerotic plaque, Fatty streak formation in human fetal aortas is enchanced by maternal hypercholesterolemia, Transmigration of monocytes, Foam cells between cap and core of a coronary atheroma, Coronary fibroatheroma, LDL modification in the arterial intima: a vicious circle, Accumulation of LDL in the arterial intima, Mast cell neutral proteases activate MMPs, Degradation of collagen, Preventing cholesterol accumulation and subsequent inflammation or even more?